2018
DOI: 10.3389/fimmu.2018.00312
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Human Contact System with Pathogens—An Update

Abstract: The name human contact system is related to its mode of action, as “contact” with artificial negatively charged surfaces triggers its activation. Today, it is generally believed that the contact system is an inflammatory response mechanism not only against artificial material but also against misfolded proteins and foreign organisms. Upon activation, the contact system is involved in at least two distinct (patho)physiologic processes:i. the trigger of the intrinsic coagulation via factor XI and ii. the cleavag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 102 publications
0
48
0
Order By: Relevance
“…86 It has been suggested that both viral and bacterial pathogens increase microvascular permeability in part through activation of the ''contact system,'' causing release of the vasoactive autacoid bradykinin. 87 Mechanisms involving endothelial Toll-like receptors 2, 4, and 9 have also been reported to be involved in the increased vascular permeability caused by bacterial infection, but these mechanisms concern pathophysiology of sepsis with no known relevance to mucosal defense. 88 Innovative in vivo approaches seem required to explore the possibility that disease-inducing microbes deposited on the intact mucosal surface can evoke highly localized plasma exudation responses.…”
Section: Antimicrobial Defense At the Surface Of An Intact Airway Mucosamentioning
confidence: 99%
“…86 It has been suggested that both viral and bacterial pathogens increase microvascular permeability in part through activation of the ''contact system,'' causing release of the vasoactive autacoid bradykinin. 87 Mechanisms involving endothelial Toll-like receptors 2, 4, and 9 have also been reported to be involved in the increased vascular permeability caused by bacterial infection, but these mechanisms concern pathophysiology of sepsis with no known relevance to mucosal defense. 88 Innovative in vivo approaches seem required to explore the possibility that disease-inducing microbes deposited on the intact mucosal surface can evoke highly localized plasma exudation responses.…”
Section: Antimicrobial Defense At the Surface Of An Intact Airway Mucosamentioning
confidence: 99%
“…This includes the modulation of important host plasma homeostatic systems such as the coagulation and fibrinolysis systems, the complement system, and the kinin generation system (also known as the contact system) [45,46,[49][50][51][52]. One of the mechanisms that facilitates the interference by pathogens of plasma homeostatic systems is the binding of their individual components to the surfaces of microbial cells, which contributes to the local increase in their concentration and further processing by proteases, or to the insidious takeover of these components and their exclusion from the host systems [53,54]. Such abilities to entrain plasma cascades and thus evade host innate immunity were previously described for the opportunistic pathogen C. albicans [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Incubation of bacteria with human plasma did not induce clotting after recalcification, suggesting that induction of blood clotting by GBS is mainly dependent on human cellular components. As certain pathogenic bacteria are able to activate the human contact system [10], bacteria were incubated with human plasma, and activation of contact system proteases at the bacterial surface was assessed. Only LUMC16 showed FXIIa/PK activity at the bacterial surface (Fig.…”
Section: Lumc16 Strain Activates Coagulationmentioning
confidence: 99%
“…The human contact system consists of two main proteases, factor XII (FXII) and plasma prekallikrein, and one nonenzymatic cofactor, highmolecular-weight kininogen. Any foreign biological or artificial surfaces activate FXII, which in turn activates coagulation factor XI (FXI), resulting in subsequent thrombus formation [10]. There is a close relationship to DIC and systemic inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%